2010
DOI: 10.7589/0090-3558-46.2.450
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Mortality in Northern Fur Seals (Callorhinus Ursinus), St. Paul Island, Pribilof Islands, Alaska, 1986–2006

Abstract: ABSTRACT:To determine whether infectious diseases might have contributed to the present-day decline of northern fur seals (Callorhinus ursinus), preweaned pups (n52,735), subadult males (n598), and adults (n5179) were examined postmortem from 1986 to 2006 on St. Paul Island, Alaska. Gross necropsy findings and histologic lesions were used to determine causes of death. Five general categories of mortality were identified for pups: emaciation (1,454 pups, 53%), trauma (497 pups, 18%), perinatal mortality (516 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 34 publications
(32 reference statements)
2
60
1
Order By: Relevance
“…Some examples of "serious scores" to illustrate the range of possible welfare insults causing severe welfare insults based on descriptions of observed seal entanglements from Spraker and Lander (2010); Severe impacts.…”
Section: Other Impacts Of Interactions With Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of "serious scores" to illustrate the range of possible welfare insults causing severe welfare insults based on descriptions of observed seal entanglements from Spraker and Lander (2010); Severe impacts.…”
Section: Other Impacts Of Interactions With Humansmentioning
confidence: 99%
“…This study found that over two-thirds of entangling materials were derived from fisheries sources. Spraker and Lander (2010) describe the causes of mortality in Northern Fur Seals (C. ursinus) on St. Paul Island, Alaska, and describe some of the horrible combinations of entanglement, asphyxiation and tissue trauma caused by net and packing band loops. In one case described, a living but heavily entangled animal is dragging a dead and decomposing seal in the same piece of net.…”
Section: Other Impacts Of Interactions With Humansmentioning
confidence: 99%
“…Concurrent bacterial pneumonia in human cardiac patients has been an accepted etiology for myocarditis since the 1940s (Saphir & Amromin 1948), but in small animal medicine, hematogenous spread of septic (usually bacterial, rarely fungal) emboli from pneumonia usually results in endocarditis with vegetative lesions adhered to the mitral and aortic valves (Kittleson 1998b). Multifocal necrotizing myopathy and cardiomyopathy has been described as a cause of death in pups of the northern fur seal Callorhinus ursinus (Spraker & Lander 2010) and affects the left ventricular, and rarely, the right ventricular free walls. The etiology is unknown at this time.…”
Section: Bpm Range 80 To 95 Bpm)mentioning
confidence: 99%
“…5,8 In a normal placenta, the rate of apoptosis increases throughout gestation; however, apoptosis can also increase in placentas during disease states, such as preeclampsia, intrauterine growth restriction, 6 and placental infections such as Toxoplasma 1 or Listeria. 5 In contrast, C. burnetii has been shown to inhibit apoptosis in host macrophages as a survival strategy.…”
mentioning
confidence: 99%
“…3 The decline of the northern fur seal (NFS; Callorhinus ursinus) population on St Paul Island, Alaska, has been well documented but is not easily explained; in a 20-year study evaluating pup mortality, the most common cause of death was trauma and nutrition, with infectious disease only infrequently identified. 8 In 2010, 75% of opportunistically collected NFS placentas from a single rookery were positive for C. burnetii by polymerase chain reaction (PCR). 4 Histologic lesions were infrequent; bacteria was visualized in 5 (3%) of the samples, and only a single placenta had arteritis.…”
mentioning
confidence: 99%